Pengaruh Pesan Kampanye Public Relations #TemanSejiwa Terhadap Brand Awarness Kopi Janji Jiwa Pada Mahasiswa Universitas Muhammadiyah Jakarta - Ahmad Mujammil Raza; Fasha Ashri Octavia; Sadiyah El Adawiyah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
In Indonesia's highly competitive local coffee shop industry, Kopi Janji Jiwa, a leading brand, utilizes public relations strategies through the #TemanSejiwa campaign to build stronger emotional connections with consumers, particularly university students. This study aims to examine the influence of the #TemanSejiwa public relations campaign messages on brand awareness of Kopi Janji Jiwa among students at Universitas Muhammadiyah Jakarta.A quantitative survey approach was employed, involving 36 purposively selected respondents—active UMJ students who are familiar with the brand and have been exposed to the campaign. Data were collected using Likert-scale questionnaires and analyzed through reliability tests (Cronbach's Alpha > 0.95), classical assumption checks, and simple linear regression.The results reveal a positive and significant effect of campaign messages on brand awareness (R² = 0.704; regression coefficient b = 0.861; p = 0.000 < 0.05). Mean scores for campaign messages (4.02) and brand awareness (4.26) on a 1–5 scale indicate strong positive perceptions of the emotional, authentic, and community-oriented messaging, which effectively enhances brand recognition, recall, and favorable associations. These findings highlight the critical role of community-based public relations strategies in strengthening the market position of local coffee brands in a competitive environment.